Peningkatan Resiliensi Petani Milenial Sleman Melalui Pendampingan Literasi Keuangan - Mustikawati, RR. Indah; Priantinah, Denies; Sari, Ratna Candra; Astuti, Vera; sayekti, Fitria Ningrum (Penerbit Widina, Widina Media Utama, 2024)
Financial literacy is an important skill that supports the welfare of the community, especially millennial farmers in Sleman, Yogyakarta. The low level of financial literacy among farmers hinders their access to financial services and effective farm business management. Therefore, a financial literacy education program is needed to improve their resilience. This research aims to improve the financial knowledge and record-keeping skills of millennial farmers in Sleman through financial literacy mentoring, and to encourage them to have better access to finance. The program was implemented through a participatory approach involving 24 farmers from various agricultural backgrounds. The methods used include lectures and hands-on practice in making simple financial reports using Microsoft Excel. This activity began with problem identification through Focus Group Discussion (FGD) and continued with training. The results of the activity implementation showed an increase in participants' understanding of the importance of financial literacy. The farmers were able to prepare simple financial statements and understand the process of cost identification and cost of goods sold calculation. The majority of participants expressed satisfaction with the training provided. Implications This financial literacy program has a positive impact in improving the financial knowledge and skills of millennial farmers in Sleman. With improved financial literacy, it is expected that farmers can better manage their businesses, improve their welfare, and contribute to the growth of the agricultural sector in Indonesia.ABSTRAKLiterasi keuangan merupakan keterampilan penting yang mendukung kesejahteraan masyarakat, terutama petani milenial di Sleman, Yogyakarta. Tingkat literasi keuangan yang rendah di kalangan petani menghambat akses mereka terhadap layanan keuangan dan pengelolaan usaha tani yang efektif. Oleh karena itu, diperlukan program pendidikan literasi keuangan untuk meningkatkan resiliensi mereka. Penelitian ini bertujuan untuk meningkatkan pengetahuan dan keterampilan pencatatan keuangan petani milenial di Sleman melalui pendampingan literasi keuangan, serta untuk mendorong mereka memiliki akses keuangan yang lebih baik. Program ini dilaksanakan melalui pendekatan partisipatif dengan melibatkan 24 petani dari berbagai latar belakang pertanian. Metode yang digunakan mencakup ceramah dan praktik langsung dalam pembuatan laporan keuangan sederhana menggunakan Microsoft Excel. Kegiatan ini dimulai dengan identifikasi masalah melalui Focus Group Discussion (FGD) dan dilanjutkan dengan pelatihan. Hasil pelaksanaan kegiatan menunjukkan peningkatan pemahaman peserta tentang pentingnya literasi keuangan. Para petani berhasil menyusun laporan keuangan sederhana dan memahami proses identifikasi biaya serta perhitungan harga pokok penjualan. Mayoritas peserta menyatakan kepuasan terhadap pelatihan yang diberikan. Implikasi Program literasi keuangan ini memberikan dampak positif dalam meningkatkan pengetahuan dan keterampilan finansial petani milenial di Sleman. Dengan peningkatan literasi keuangan, diharapkan petani dapat mengelola usaha mereka dengan lebih baik, meningkatkan kesejahteraan mereka, serta berkontribusi pada pertumbuhan sektor pertanian di Indonesia.